Scapular kinematics during unloaded and maximal loaded isokinetic concentric and eccentric shoulder flexion and extension movements - Wochatz, M.; Rabe, S.; Engel, T.; Mueller, S.; Mayer, F. (Journal of Electromyography and Kinesiology, 2021)
Characterization of scapular kinematics under demanding load conditions might aid to distinguish between physiological and clinically relevant alterations. Previous investigations focused only on submaximal external load situations. How scapular movement changes with maximal load remains unclear. Therefore, the present study aimed to evaluate 3D scapular kinematics during unloaded and maximal loaded shoulder flexion and extension. Twelve asymptomatic individuals performed shoulder flexion and extension movements under unloaded and maximal concentric and eccentric loaded isokinetic conditions. 3D scapular kinematics assessed with a motion capture system was analyzed for 20° intervals of humeral positions from 20° to 120° flexion. Repeated measures ANOVAs were used to evaluate kinematic differences between load conditions for scapular position angles, scapulohumeral rhythm and scapular motion extent. Increased scapular upward rotation was seen during shoulder flexion and extension as well as decreased posterior tilt and external rotation during eccentric and concentric arm descents of maximal loaded compared to unloaded conditions. Load effects were further seen for the scapulohumeral rhythm with greater scapular involvement at lower humeral positions and increased scapular motion extent under maximal loaded shoulder movements. With maximal load applied to the arm physiological scapular movement pattern are induced that may imply both impingement sparing and causing mechanisms.